STUDI INOVASI SAKERA JEMPOL DI KABUPATEN PASURUAN - Yusrin Rahmawati; Erva Mutiara Hati; Indah Lukmawati (Dialogue : Jurnal Ilmu Administrasi Publik, 2020)
Cases of violence against women and children that still occur in Indonesia, including in Pasuruan Regency, made the government innovate Sakera Jempol in an effort to deal with cases of violence against women and children. The purpose of this research is that the writer wants to find Sakera Jempol innovations made by the government in an effort to overcome the challenges. In this study, researchers used a method of research literature studies. Sakera Jempol's innovation in Pasuruan Regency has received an award from the Ministry of PAN-RB as the best national public servant and has succeeded in promoting the safety of girls in Pasuruan Regency.